Research on preparation of titanium powders used for metal additive manufacturing - GUO Guang-hao; TANG Chao-lan; CHU Rui-kun (Fenmo yejin jishu)
Metal additive manufacturing technology is now developing in the direction of industrialization, and the titanium powders are one of the mainstream raw materials used for metal additive manufacturing. The smelting technology of titanium and its alloys was summarized in this paper, the induction smelting was emphasized, and the main technology of titanium powder preparation was analyzed and compared, including the basic principles, the characteristics, and the factors affecting the powder characteristics. In addition, the application of numerical simulation on the titanium powder preparation was also introduced, and the development of titanium powder preparation technology used in the field of metal additive manufacturing was prospected.